Extraction of sulfated polysaccharides from the tegument of sea cucumber Pattalus mollis - Gonzáles, Diego (2019)
Polysaccharides isolated from Pattalus mollis (PPM) were obtained by the method of enzymatic hydrolysis and by precipitation with ethanol. A component analysis was carried out, which consisted in the determination of the content of sulfates, total sugars and total proteins by conventional methods. The objective of this study was to obtain the polysaccharides by enzymatic hydrolysis. The enzyme papain was used to break peptide bonds and ethanol to precipitate polysaccharides. The content of sulfates, total sugars and proteins was 2.36, 2.83 and 22.3%, respectively.